2015
DOI: 10.2105/ajph.2012.301021r
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Racial Disparities in Infant Health in Brazil

Abstract: Objective-Racial disparities in infant health are common in Brazil. Explaining these disparities and identifying the pathways through which they arise is essential for identifying risk factors that can be targeted by policy interventions. Our objective is to quantify the extent to which socioeconomic, healthcare, demographic, and geographic effects explain racial disparities in low birth weight (LBW) and preterm birth (PTB) rates in Brazil.Methods-We employ a sample of 8949 infants born between 1995 and 2009 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…As a limitation of this study, the non-inclusion of the skin color variable, still limited in the information systems, especially in SIM 4 , may have prevented a better understanding of the interrelationships between these sociodemographic factors 2 . However, based on other studies that analyzed the same variables, we believe that, even with adjustment for skin color, age and education would continue to have magnitude and statistical significance 17 .…”
Section: Discussionmentioning
confidence: 90%
“…As a limitation of this study, the non-inclusion of the skin color variable, still limited in the information systems, especially in SIM 4 , may have prevented a better understanding of the interrelationships between these sociodemographic factors 2 . However, based on other studies that analyzed the same variables, we believe that, even with adjustment for skin color, age and education would continue to have magnitude and statistical significance 17 .…”
Section: Discussionmentioning
confidence: 90%
“…However, we would caution against such an over-interpretation of the unexplained variation. For instance, in their decomposition analysis in Brazil where a spectrum of genetic admixtures could be studied, Nyarko, et al ( 2014 ) found individual, household, medical, and geographic factors could explain up to 94% of the disparity. Moreover, the decomposition analysis approach highlights the fact that unexplained variation can be due to factors such as variable parameterization and not only unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…The “myth of racial democracy” that Brazil has reduced degrees of racial discrimination is very prevalent. Thus, the role of the racial component in generating and maintaining the very high levels of inequality in Brazilian society may be underestimated ( 2 , 10 ).…”
Section: Introductionmentioning
confidence: 99%